1996
DOI: 10.1089/lps.1996.6.61
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Hernia of Foramen of Morgagni: A New Case Report

Abstract: A new case report of laparoscopic repair of a diaphragmatic hernia through the foramen of Morgagni in a 53-year-old woman is described. The patient had a successful recovery with no recurrence 2 years after surgery. The authors propose that the laparoscopic approach is an alternative to classical treatment for this kind of hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…After this report, this kind of hernia bore his name [14]. As for the age of CMDH diagnosis, there are recent retrospective studies on CMDH, mostly representing adult data and only few series focused on children [4][5][6][7][8][9]. In the majority of cases, patients with CMDH are asymptomatic, and the pathology is often diagnosed incidentally during a chest X-ray performed for other indications [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this report, this kind of hernia bore his name [14]. As for the age of CMDH diagnosis, there are recent retrospective studies on CMDH, mostly representing adult data and only few series focused on children [4][5][6][7][8][9]. In the majority of cases, patients with CMDH are asymptomatic, and the pathology is often diagnosed incidentally during a chest X-ray performed for other indications [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 15-years with the advent of laparoscopic surgery, several cases underwent laparoscopic repair which have been reported in the surgical literature both in adults and children [4][5][6][7][8][9][10]. Due to the rarity of this condition, there is no consensus about the gold standard laparoscopic technique to be adopted and various approaches have been reported until now [11][12][13].The aim of this study is to evaluate the surgical and clinical outcomes of children who underwent laparoscopic correction of CMDH in 8 international centers of pediatric surgery, in order to standardize the surgical correction technique of this rare pathology.…”
mentioning
confidence: 99%
“…Whether the hernial sac should be excised is a controversial issue. Fernandez et al [4] and Rau et al [11] recommend excision of the hernia sac, whereas others prefer to leave it [12,13]. In our series, we elected to plicate the sac within the repair avoiding the possible injuries to the pericardium, pleura, or phrenic nerve that might be associated with the sac excision.…”
Section: Discussionmentioning
confidence: 98%
“…The method of laparoscopic closure of the defect and the excision of the sac are debatable. Lima et al [3] recommended primarily closure with a continuous suture, Fernandez et al [4] recommended using interrupted sutures with intracorporeal knot tying, and Ramachandran et al [5] suggested placement of a mesh. Laparoscopic-assisted repair of Morgagni hernia by taking full thickness of anterior abdominal wall in a U-shaped stitch under direct vision with extracorporeal knot tying in the subcutaneous tissue is another option [6].…”
mentioning
confidence: 99%
“…The method of laparoscopic closure of the defect and the excision of the sac are debatable. 6 Many technique has been described as primarily closure with a continuous suture by Fernandez et al, 7 interrupted sutures with intracorporeal knot tying, and Ramachandran et al 8 laparoscopic-assisted repair of MH by taking full thickness of anterior abdominal wall in a U-shaped suture under direct vision with extracorporeal knot tying in the subcutaneous tissue is also scribed. 9,10 I used laparoscopic two ports and Sorze port closure needle to insert U-shape sutures to close the defect in MH of infant and children without excision of the sac or insertion of chest drain.…”
Section: 5005/jp-journals-10033-1181mentioning
confidence: 99%